EFEKTIVITAS ABSENSI ELEKTRONIK TERHADAP DISIPLIN DAN KINERJA PNS DI LINGKUNGAN PEMERINTAH KABUPATEN KUTAI KARTANEGARA - Toni Nurhadi Kumayza (Prodi Administrasi Negara FISIPOL Universitas Kutai Kartanegara, 2017)
Employee dispensation is an important issue for local government apparatus to improve employee performance, the issuance of regent regulation no 46 of 2013 on discipline of employees in the environment of Kutai Kartenagara district government has consequences for high fees to form discipline behavior, but the reality of the field is different from the expected, While the establishment of disciplinary behavior is supported by the use of fingerprint attendance devices.Key word: discipline, performance